Critical success factors of Lean Six Sigma from leaders’ perspective - Alnadi, Mohammad Mahmmud; McLaughlin, Patrick (Emerald, 2021)
Purpose – This paper aims to provide a synthesis of the results of the previous literature on leadership behaviours that enable successful Lean Six Sigma implementation. Design/methodology/approach – The published literature that relates to leadership and Lean Six Sigma has been included. A thematic analysis was conducted on the previous literature which helped in identifying the relevant aspects and associating the behaviours with specific aspects. Findings – After analysing the literature, seven key aspects have emerged: (1) communication; (2) culture of continuous improvement; (3) coaching and developing employees; (4) creating vision and aligning goals; (5) employee motivation; (6) employee empowerment; (7) leadership commitment and support. The main leadership behaviours that facilitate and support Lean Six Sigma implementation have been summarised. Originality/ value – Thematic analysis in this field is scarce, so identifying the leadership behaviours’ themes can help researchers in developing a framework of leadership behaviours. Organisations and practitioners of Lean Six Sigma can take into consideration these behaviours as a key to the successful implementation of Lean Six Sigma. They can adjust their behaviours and know the behaviours that need to be developed among leaders. This would facilitate the Lean Six Sigma journey by overcoming the challenges that face practitioners during Lean Six Sigma implementation.